Political and civil rights of non-Muslims in an Islamic State in the light of the Qur'an and Sunnah: Malaysia as a case study / Nasser A.O. Abdaljawwad - Nasser A.O., Abdaljawwad (2017)
This study deals with political and civil rights of non-Muslims in the Islamic State and the origin of these rights from the perspective of Islamic law. It provides an important basis and theory about these rights. It asserts that Islam is always very much tolerant, lenient and just in the matter of any transactions and relationships between Muslims and non-Muslims in general, and political and civil rights, in particular. It argues that the legal provisions, existing and emerging on the subject, should be considered in the light of this fact. Any departure from this rule shall be considered abnormal (and so of no effect). (In other words,) it must be subject to the original rule (of tolerance, leniency and justness). This research claims that Islam regulates the relationships of Muslims and non-Muslim minorities in the Islamic community in an exemplary manner striking a balance between maintaining the purity and superiority of Islamic law, and giving the minorities full civil and political rights, far from being extreme or excessive, relying mainly on the Qur’an and the Sunnah, then the general rules of law and jurisprudence, while not neglecting the practical application of this theory throughout the Islamic history. Therefore, this work has examined the evidences (Texts) of the Qu’ran, Sunnah (Prophet’s Traditions) and Athar (Practices of the Sahabah), and, classifying them by their strength, devised general rules and principles firmly based on them. In addition, this study describes the level of compatibility of Islamic law with international law and the principles of human rights as endorsed by the international bodies and United Nations Organization and (other bodies) relating to civil and political rights for minorities. (It underscores that) that there is a need to take into account the new situation in the current era on the subject of minorities jurisprudence. It is also needed to redefine fiqh of the past, which was developed by the specific circumstances of our predecessors' time, appropriate to the current situation based on Al-Qur’an and hadith and without any with conflict with the rules and objectives of Shari’ah. Finally, the results obtained by the researcher in this study are based on interviews with an important part of non-Muslim citizens of Malaysia (Buddhist, Hindu, Christian and other, representing 40% of total population) about their views on political and civil rights they are enjoying as a contemporary example and unique experience from Malaysia for in the rest of the Muslim world.